2017
DOI: 10.1093/jisesa/iex008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nest Box Distribution on Sustainable Propagation of Osmia lignaria (Hymenoptera: Megachilidae) in Commercial Tart Cherry Orchards

Abstract: The blue orchard bee, Osmia lignaria (Say), is a solitary bee that is an excellent pollinator of tree fruit orchards. Due to the annual rising costs of honey bee hive rentals, many orchardists are eager to develop management tools and practices to support O. lignaria as an alternative pollinator. Establishing O. lignaria pollination as a sustainable industry requires careful consideration of both bee and orchard management. Here, we test the effect of artificial nest box distribution on in-orchard propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Metrics from the census included the number of cells with viable progeny, proportional mortality of cells, female‐to‐male sex ratio, average cells produced per tunnel, proportion of bees that died during development, proportion of cells occupied by parasites and/or scavengers, and the proportion pollen ball, which are cells with uneaten provisions on which no progeny had developed (Boyle & Pitts‐Singer, ; Pitts‐Singer et al, ). Sex, cause, and stage of death were determined by evaluating the relative size, position, and contents of cocoons within a given nest (pictured in Boyle & Pitts‐Singer, ). Because weather and specific strategies for in‐orchard management varied by year, cross‐year comparisons were not conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metrics from the census included the number of cells with viable progeny, proportional mortality of cells, female‐to‐male sex ratio, average cells produced per tunnel, proportion of bees that died during development, proportion of cells occupied by parasites and/or scavengers, and the proportion pollen ball, which are cells with uneaten provisions on which no progeny had developed (Boyle & Pitts‐Singer, ; Pitts‐Singer et al, ). Sex, cause, and stage of death were determined by evaluating the relative size, position, and contents of cocoons within a given nest (pictured in Boyle & Pitts‐Singer, ). Because weather and specific strategies for in‐orchard management varied by year, cross‐year comparisons were not conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainable in‐orchard reproduction of O. lignaria in commercial orchards for use during the following year is not always achieved (Artz, Allan, Wardell, & Pitts‐Singer, , ). Except for the occasion when in‐orchard progeny recovery exceeds the number of O. lignaria initially released (Boyle & Pitts‐Singer, ; Pitts‐Singer et al, ), most O. lignaria currently available for distribution are captured from natural environments, which may have repercussions on native populations and their contributed ecosystem services to wildlands (Tepedino & Nielson, ). Additionally, trapping bees is labor‐intensive, and management practices for the processing and cleaning of cocoons to eliminate pests and diseases can be costly.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have demonstrated that Bombus terrestris is an effective pollinator of raspberries and tomatoes (Ahmad et al, ; Willmer, Bataw, & Hughes, ). Regarding mason bees, different studies have focused on the efficiency of mason bees, such as Osmia cornuta (Márquez, Bosch, & Vicens, ; Monzón, Bosch, & Retana, ; Vicens & Bosch, ) and Osmia lignaria ( Artz, Allan, Wardell, & Pitts‐Singer, ; Boyle & Pitts‐Singer, ; Koh, Lonsdorf, Artz, Pitts‐Singer, & Ricketts, ) . The potential competition between different species of bumble bees ( Bombus vosnesenskii and Bombus melanopygus) and mason bees ( O. lignaria ) with the honey bee has been examined in at least one study, carried out in California by Brittain, Williams, Kremen, and Klein () in an almond orchard; these authors found no evidence of competition but rather an enhancement of the pollination activity of A. mellifera .…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the biggest challenge for commercial-scale pollination by O. lignaria has been their limited supply. Growing public interest in wild and alternative bees over the past decade has led to the development of a competitive O. lignaria-based industry, from which the necessary quantities of bees are now available for field-scale trials and uses (Boyle & Pitts-Singer 2017, Andrikopoulos & Cane 2018, Pitts-Singer et al 2018, Pinilla-Gallego & Isaacs 2018). Recent studies have and continue to identify the crops and geographic regions in which managed O. lignaria populations best perform.…”
Section: Introductionmentioning
confidence: 99%